Venetoclax in combination with hypomethylating agents in previously untreated patients with acute myeloid leukemia ineligible for intensive treatment: a real-life multicenter experience. (March 2022) - De Bellis, Eleonora; Imbergamo, Silvia; Candoni, Anna; Liço, Albana; Tanasi, Ilaria; Mauro, Endri; Mosna, Federico; Leoncin, Matteo; Stulle, Manuela; Griguolo, Davide; Pravato, Stefano; Trentin, Livio; et al.
Abstract: The addition of venetoclax to hypomethylating agents (HMA-V) improved the outcome of patients with newly diagnosed acute myeloid leukemia (AML) ineligible for intensive treatment. The aim of our study was to confirm data reported in literature, in a real-life multicenter experience. We retrospectively evaluated 56 naïve AML patients who received HMA-V at 8 different collaborating Hematology Units in the North-East of Italy, from September 2018 to October 2020. Patients received azacitidine or decitabine at standard dose, adding venetoclax starting from cycle 1–3. The median time-to-response was 2 cycles and composite complete remission rate (CCR) was 67.9%. Thirteen out of 38 responders (34.2%) relapsed, with a median response duration of 13.7 months. Transfusion independence (TI) was obtained in 27 (87.0%) and 28 (90.3%) out of 31 patients for red blood cells and platelets, respectively. Median OS was 12.3 months (95% CI, 8.1–16.5), and median PFS was 11.3 months (95% CI, 4.6–17.9). Cytogenetic risk was the only variable impacting on survival, while no differences were observed stratifying patients by age, bone marrow blasts, WHO classification or type of HMA. In conclusion, our real-life multicenter experience indicates that HMA-V treatment allows achieving good response rates in naïve AML patients, ineligible for intensive chemotherapy. Highlights: HMA-V is a treatment option for naïve AML patients unfit for intensive chemotherapy. In our real-life multicenter experience, 56 unfit naïve AML patients received HMA-V. ORR was 67.9%, and incidence of relapse was 34.2% with a median RD of 13.7 months. Median OS was 12.3 months, and cytogenetic resulted to have an impact on survival.